Landscape of targeted therapies for lung squamous cell carcinoma - Chen, Qiuxuan; Zheng, Xiaoshuo; Li, Jian (Frontiers in Oncology, 2024)
Lung cancer, a common type of malignant neoplasm, has seen significant advancements in the treatment of lung adenocarcinoma (LUAD). However, the management of lung squamous cell carcinoma (LSCC) continues to pose challenges. Traditional treatment methods for LSCC encompass surgical resection, chemotherapy, and radiotherapy. The introduction of targeted therapy and immunotherapy has greatly benefited LSCC patients, but issues such as limited immune response rates and adverse reactions persist. Therefore, gaining a deeper comprehension of the underlying mechanisms holds immense importance. This review provides an in-depth overview of classical signaling pathways and therapeutic targets, including the PI3K signaling pathway, CDK4/6 pathway, FGFR1 pathway and EGFR pathway. Additionally, we delve into alternative signaling pathways and potential targets that could offer new therapeutic avenues for LSCC. Lastly, we summarize the latest advancements in targeted therapy combined with immune checkpoint blockade (ICB) therapy for LSCC and discuss the prospects and challenges in this field.